Chapter 1 Migration, civil society and global governance An introduction to the special issue - Schierup, Carl-Ulrik (Rethinking Globalizations, 2019)
The current special issue examines the development of an emerging global governance on migration and the spaces, roles, strategies and alliancemaking of a composite transnational civil society engaged in issues of rights and the protection of migrants and their families. This question is connected with how different actors - the United Nations, international organizations, governments and a wide variety of civil society organizations and regional and global trade unions - perceive the root causes of migration, global inequality and options for sustainable development. The contributions included in the special issue interrogate from different perspectives the positionality and capacity of civil society to influence the Global Forum for Migration and Development. They examine the opportunities and challenges faced by civil society in its endeavor to promote a rights-based approach within international and intergovernmental fora engaged in setting up a global compact for the management of migration and in other global policy spaces.